EL RECLUTAMIENTO ILEGAL DE LOS MENORES EN COLOMBIA Y SU RESPONSABILIDAD PENAL DENTRO DEL CONFLICTO ARMADO (2016)
This document is the result of an analytical study on the main discussions and reflections developed around the problem of forced recruitment children in Colombia, identifying as central axis of questioning, the debate over the defense or opposition to the criminalization and to the recognition of the criminal responsibility of children recruited by the armed actors in the conflict, and subsequently disconnected from it